2012
DOI: 10.3168/jds.2012-5866
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Oxidative status and incidence of mastitis relative to blood α-tocopherol concentrations in the postpartum period in dairy cows

Abstract: Vitamin E supplementation, when combined with high blood α-tocopherol (>6.25 μg/mL) at dry off, has been reported to unexpectedly increased the risk for clinical mastitis in dairy cows. Furthermore, higher levels of oxidative stress in the postpartum period were related to higher risk of mastitis. The objective of the present study was to determine the relationship between various serum biomarkers of oxidative status, incidence of mastitis, and blood α-tocopherol concentrations at dry off and at calving. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 12 publications
4
19
0
3
Order By: Relevance
“…Milk yield and quality are critical determinants of a cow's dairy value (Politis, 2012). In the current study, the absorption of by-products of phenolic digestion could have reduced inflammation caused by stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Milk yield and quality are critical determinants of a cow's dairy value (Politis, 2012). In the current study, the absorption of by-products of phenolic digestion could have reduced inflammation caused by stress.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamins, mostly A, C and E, and minerals, such as selenium, copper and zinc, have been used to mitigate oxidative stress (Politis et al, 2012). However, in confined systems, the risk of over-or undersupplying micro elements is high (Bouwstra et al, 2010), hence the overproduction of pro-oxides is common (Rizzo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent work, they demonstrated that cows with higher BCS prepartum and greater BCS loss postcalving had higher concentrations of reactive oxygen metabolites, thiobarbituric acid reactive substances, and thiol groups and lower plasma superoxide dismutase activity and erythrocyte thiol groups postpartum, collectively suggestive of increased oxidative stress in cows of higher BCS and with greater BCS loss postcalving concurrent with higher NEFA and BHB concentrations postpartum in the same group (Bernabucci et al, 2005). More recently, Politis et al (2012) reported that concentrations of α-tocopherol in cows receiving high dietary levels of vitamin E (3,000 IU/d) during the dry period were inversely related with concentrations of serum reactive oxygen metabolites and thiol groups at dry-off and calving; however, these markers of oxidative stress were not related to subsequent development of mastitis.…”
Section: Putative Indicators Of Oxidative Stress and Inflammationmentioning
confidence: 94%
“…All of the studies above that have focused on indicators of oxidative stress and inflammation, with the exception of Huzzey et al (2011Huzzey et al ( , 2015, Politis et al (2012), andPohl et al (2015), were conducted using small (generally 100 cows or less) data sets, and studies that had larger numbers of cows were conducted in 1 or 2 dairy herds. To date, we lack the type of information for these indicators that has been gleaned from largescale observational studies described above that related NEFA and BHB to outcomes across many herds with many cows.…”
Section: Putative Indicators Of Oxidative Stress and Inflammationmentioning
confidence: 99%
“…In these periods the energy requirement significantly increases, essentially to support milk production, and the physiological adaptation to this condition is represented by the implementation of metabolic activities and by an extensive mobilization of body fat reserves, particularly in early lactation. The accumulation of triglycerides in the liver and the increase of lipid metabolites concentration in the blood result in the enhancement of ROS production, decrease of paraoxonase activity, and onset of oxidative stress (Turk et al, 2008;Morris et al, 2009;Pilarczyk et al, 2012), which in turn leads to a higher vulnerability of dairy cows to bacterial infections (Kehrli et al, 1989;Mallard et al, 1998;Keane et al, 2006;van Knegsel et al, 2007), thus causing metabolic disorders and diseases (LeBlanc et al, 2004;Rizzo et al, 2007Rizzo et al, , 2009LeBlanc, 2008;Sharma et al, 2011;Politis et al, 2012;Sordillo and Raphael, 2013;Wathes et al, 2013).…”
Section: Discussionmentioning
confidence: 99%